Jugoslavenski Jadran - Zdunić, Drago; Kinert, Albert; Dabac, Tošo; Zuber, Vilko; Grčević, Mladen; Pavić, Milan, fotograf; Gattin, Nenad (Grafički zavod Hrvatske, 1963)
Fotomonografija Jadranskog mora.